Critical Considerations for Optimizing the Support for International Student Engagement - Tran, Ly; Blackmore, Jill; Forbes-Mewett, Helen; Nguyen, Diep; Hartridge, Danielle; Aldana, Renata (Journal of International Students, 2022)
Hosting international students enriches the educational, intercultural, social, political and economic capitals of the host communities. It is therefore a significant privilege and opportunity for education providers and host countries to educate students from other countries. But it is also the host communities’ responsibility to nurture an optimal education experience for this cohort, which in turn helps strengthen international education for all. Student engagement is vital for creating a welcoming, caring and positive experience for international students.